ON THE ISSUE OF PREVENTION OF INFECTIOUS COMPLICATIONS IN WOMEN AFTER SURGICAL DELIVERY - Анастасия Владимировна Неклюдова; Маргарита Викторовна Андреева; Элеонора Борисовна Белан; Анатолий Евгеньевич Мирошников (The Publishing House Medicine and Enlightenment, 2023)
Objective of the study - improvement of the course and reduction in the frequency of complications of the early postoperative period in puerperas after caesarean section with the help of a comprehensive, including non-drug prophylaxis. Materials and research methods. We examined 97 puerperas after caesarean section in the early postoperative period of the Volgograd region for the period from 2020 to 2022. All puerperas were divided into 2 clinical groups. Group 1 (main) consisted of 47 patients who, along with the generally accepted management of the postoperative period, underwent a general universal rehabilitation program using 10 quantum therapy impact zones and local application of quantum therapy to the area of the postoperative wound. Group 2 (comparison) included 50 puerperas with traditional management of the postoperative period without the use of quantum therapy. Research results. Clinical laboratory and special research methods have proved that quantum therapy in puerperas from the first day after cesarean section, in addition to traditional management, improves the course of the postoperative period: it increases the adaptive capabilities of the female body, improves the functional state of the autonomic nervous system, normalizes the psycho-emotional status of patients, reduces the frequency of infectious complications, which ultimately leads to an improvement in the quality of life of women.